Interactive Multimedia in Inquiry Learning: Analyzing Population Dynamics for Critical Thinking - Lia Kurnia Umi; Yuswanti Ariani Wirayahu; Alfyananda Kurnia Putra (Abjadia, 2021)
Inquiry learning is learning that requires students to be active and independent. Inquiry-based learning was developed for critical teaching and learning to students. Critical thinking skills that need to be developed in students, because it provides an understanding of a problem in a material and to be able to make decisions in everyday life. This study aimed to determine the effect of an android-based interactive multimedia-assisted inquiry learning model on students' critical thinking skills. This research is a quasi-experimental research with posttest only control group design. The research subject is SMA Brawijaya Smart School Malang, with class XI IPS 5 as the experimental class and XI IPS 6 as the control class. The instrument used is an essay test with indicators of critical thinking skills. The data analysis technique used is the independent sample t-test. The results showed that interactive multimedia-assisted inquiry learning based on Android affected essential thinking skills in the population dynamics material. This is evidenced by the average value of the experimental class with inquiry learning which has a higher value of 81,07 compared to the control class with the conventional model, which is 76,34.